(untitled) (Surkhet Journal, 2025)
This research examines how the Raji community in Chaukune Rural Municipality, Surkhet District which is one of Nepal’s most economically marginalized and endangered indigenous communities, the Raji, confront several socioeconomic difficulties. This study employed a descriptive research design to investigate the socio-economic, educational, and livelihood indicators related to the practice of social security allowance in the Raji community of Chaukune Rural Municipality, Surkhet. The study area was purposively selected based on the presence of the Raji community. The total population included 37 Raji households, all of which were sampled using a purposive sampling method. The study examines how the SSA impacts their means of subsistence, spending patterns, and access to essential services using primary data. The results show that the allowance is a vital source of funding that enables users to cover costs for things like food, medical care, and education. The paper also highlights the ways in which collective endeavors, such as cooperatives, support the preservation of cultural identity and strengthen interpersonal relationships. The study highlights the importance of social protection programs in reducing economic vulnerability and promoting welfare in marginalized communities. The Raji community’s increasing feeling of economic and social resilience is demonstrated by the use of SSA for small companies, cooperative savings, and cultural preservation projects. SSA must be combined with more comprehensive development programs, such as focused educational endeavors, healthcare advancements, and livelihood diversification, in order to achieve long-term socioeconomic upliftment in order to ensure sustained growth for the Raji community, it will be imperative to address these structural concerns through inclusive policies.